Consecrated Virgins in Italy: A Case Study in the Renovation of Catholic Religious Life - Turina, Isacco (Journal of contemporary religion, 2011)
Catholic religious life has undergone major changes since the Second Vatican Council. These have to do with the relationship between the individual and the institution and the place of consecrated people in contemporary society, among other issues. This article focuses on the consecration of virgins. It is a very ancient rite, re-established by the Church in 1970. The women make a public promise of perpetual virginity. They do not belong to any religious order. Their distinctive feature is a secular lifestyle: they live alone or with their parents, have secular jobs and ordinary relationships with friends, colleagues, and parishioners, and do not wear a veil or any religious habit. There are about 400 consecrated virgins living in Italy today. In this empirical study, emphasis is placed on their work and their (sometimes difficult) relations with the institutional church.